Long-Term Risk of Incident Arrhythmias Associated With Early Repolarization Pattern ― The Atherosclerosis Risk in Communities (ARIC) Study - He, Qian; Liao, Yi-Jian; Wang, Jin-Jie; Chen, Yan-Lin; Huang, Min-Jing; Lin, Mei-Ping; Zhou, Hai-Ling; Chen, Zi-En; Wu, Qian; Lu, Si-Long; Wu, Shu-Lin; Xue, Yu-Mei; et al. (Circulation Journal, 2025)
Background: The early repolarization pattern (ERP) is associated with cardiovascular death, but its connection with arrhythmias remains unknown. This study evaluated relationships between ERP and incident arrhythmias, including ventricular arrhythmias, bradyarrhythmias, and atrial fibrillation (AF)/flutter (Afl).Methods and Results: We analyzed 14,679 middle-aged (45–64 years) participants from the Atherosclerosis Risk in Communities cohort, a prospective population-based study in the US. Participants were monitored for ERP status at baseline and at 3 subsequent follow-up visits. We examined associations between incident arrhythmias and baseline ERP, time-varying ERP, time-updated ERP, and changes in ERP over time using Cox models to estimate hazard ratios (HRs) adjusted for potential confounders. Over a 20-year follow-up, there were 1,252 ventricular arrhythmias, 890 bradyarrhythmias, and 2,202 cases of AF. Time-updated ERP was associated with increased HRs for ventricular arrhythmias (1.55; 95% confidence interval [CI] 1.35–1.77), bradyarrhythmias (1.76; 95% CI 1.48–2.08), and AF (1.25; 95% CI 1.10–1.43). Time-varying ERP also showed associations with these outcomes. Compared with individuals with consistently normal electrocardiogram results, those with new-onset or persistent ERP had increased risks of incident arrhythmias. In subjects with time-updated ERP, anterior leads and J wave amplitudes ≥0.2 mV were associated with a higher incidence of arrhythmias.Conclusions: Several types of ERP, including time-varying, time-updated, new-onset, and consistent, are associated with the incidence of arrhythmias in the middle-aged biracial (Black and White) population.